Octadentate flexible ligands as a platform for a variety of homo and heterometallic complexes containing diphenoxido and phenoxido/azido bridging groups: synthesis, structure and magnetic properties. (28th March 2018) - Pramanik, Koushik; Malpaharia, Pijush; Colacio, Enrique; Das, Babulal; Chandra, Swapan K.
Abstract : Homometallic (M2 and M4 ) and heterometallic (Ni4 Cu) complexes were assembled from octadentate Schiff-base ligands, transition metal ions and ancillary ligands. Abstract : We have synthesised a family of N5 O3 octadentate ligands, H3 L1, H3 L2 and H3 L3, which only differ in the substituent of the salicylaldehyde moiety (H for H3 L1; 5-OMe for H3 L2 and 5-NO2 for H3 L3). These ligands react with Cu II, Ni II and Mn II to produce non-symmetrical dinuclear Cu2, Ni2 and Mn2 species, in which metal ions are connected by a double phenoxide bridging group. Sequential reaction of H3 L1 with Ni II and azide afforded a heterobridged tetranuclear compound [Ni4 (L1)2 (μ-N3 )(H2 O)2 ]ClO4 ·3H2 O, in which two diphenoxido bridged dinuclear Ni2 units are linked by an end-to-end azido bridging group. The reaction of H3 L2 with Ni II and subsequently with Cu II and azide afforded a heteropentametallic (Ni4 Cu) compound in which two diphenoxido bridged dinuclear Ni2 units are linked to the central Cu II atom through phenoxido/1, 1-azido double bridges. Characterisation was done by spectroscopic, ESI-MS +, analytical techniques including single crystal X-ray structure analyses, and magnetic measurements. The six dinuclear complexes exhibit weak antiferromagnetic (AF) interactions through the double phenoxido bridging group. The Ni4 complex shows weak AF interactions inside the Ni2 dinuclear units and medium to strong AF interactions between these Ni2 units transmitted by the 1, 3- azido bridging group. However, the pentanuclear heterometallic complex (Ni4 Cu) shows ferromagnetic interactions through all the magnetic pathways.